Corporate stakeholder democracy : politicizing corporate social responsibility - Braun, Róbert, 1966- (Central European University Press, 2019)
"Most practitioners and decision makers look at corporate social responsibility (CSR) as a socially responsible management practice on top of what company leaders generally do: focus on the sustainable, long term financial profitability of their corporation. This book focuses on a political understanding of CSR: the author bridges politics with corporate social responsibility and in a creative and provocative manner. Braun seeks to explore why and how corporations are to be seen as political actors with important roles in our current societies."--